Typological characteristics of interlanguage: Across L2 modalities and proficiency levels - Hao, Yuxin; Xu, Xuan; Wang, Xuelin; Lin, Yanni; Liu, Haitao (Frontiers in Psychology, 2023)
In recent years, quantitative methods have been increasingly used in interlanguage studies, but these studies have mostly focused on the micro level with an emphasis on certain syntactic structures, rather than the macro where interlanguage is perceived as a whole. There remains a paucity of quantitative studies on interlanguage from the typological perspective. With the majority of the studies focused on the written interlanguage, there is also a lack of sufficient research on its spoken modality. Based on a syntactically annotated corpus and using the quantitative linguistic metric of dependency direction, we have investigated the typological changes in the Chinese interlanguage in both written and spoken modalities. The findings are as follows: (1) the typological features of interlanguage vary across modalities at both macro and micro levels; (2) dependency direction is proved to be an inappropriate indicator to measure the general typological characteristics of interlanguage development due to its failure to reflect the changes in the spoken modality; (3) both macro and micro perspectives taken into consideration, typological errors in the interlanguage is more likely to occur in the spoken modality than in the written one, in which learners may be restricted by greater time pressure and cognitive load in utterance. These factors may affect the distribution of dependency direction in the oral modality, and may be the reason why it is not appropriate to use dependency direction as a measure of changes in mediated language typological features in the oral modality. It is expected that our study will bring insight into second language research with more objective and holistic evidence.